Development of the structure of a computerized information and measurement system based on the analysis of the problems of using an asynchronous electric drive in pumping equipment - Yu.O. Podchashynskyi; Ya.V. Mahaletskyi (Технічна інженерія)
The article analyzes the features of using an asynchronous electric drive in pumping equipment. Focusing on the problems that arise in the diagnosis, research and maintenance of such engines, in particular in electro-hydraulic systems, the study uses information from an authorized service center "GRUNDFOS" and relevant scientific studies. The unique requirements of these systems, including severe start-up conditions and variable load profiles, emphasize the need for robust equipment diagnostics and maintenance systems.